Fashion thinking : creative approaches to the design process - Dieffenbacher, Fiona (Bloomsbury Visual Arts, Bloomsbury Publishing Plc, 2021)
"An investigation into the creative design process, following a number of award-winning student fashion designers through the development of their final collections. By following ten award-winning student designers through their thought processes in response to a brief, Fashion Thinking establishes key approaches to design and encourages this process of discovery. Each student project represents a diverse range of strategies at each stage of the design cycle. By following each stage of development, these examples offer a unique and inspiring insight into the thinking behind a final collection. Supported by beautiful imagery and illuminating perspectives from professionals throughout the fashion industry, Fashion Thinking is a book that no aspiring fashion designer should be without!"-- Provided by publisher.
Keywords: Fashion design.; elektronické knihy; electronic books